(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Teaching and learning should be a two way process, which should underpin appropriate behavior and respect for everyone in the group. Having the rules visible to everyone acts as a reminder as to what has been agreed by the group. It is imperative that student feels relaxed within the learning environment. The room should be well laid out, have a comfortable temperature, with good lightening. Opening the training with an ice breaking session (come dine with me words well-planning the menu and famous guests).